Magnetic clouds along the solar cycle: Expansion and magnetic helicity - Dasso, S. (2011)
Magnetic clouds (MCs) are objects of extreme importance in the heliosphere. They have a major role on releasing magnetic helicity from the Sun (with crucial consequences on the solar dynamo), they are the hugest transient object in the interplanetary medium, and the main actors for the Sun-Earth coupling. The comparison between models and observations is beginning to clarify several open questions on MCs, such as their internal magnetic configuration and their interaction with the ambient solar wind. Due to the decay of the solar wind pressure with the distance to the Sun, MCs are typically in expansion. However, their detailed and local expansion properties depend on their environment plasma properties. On the other hand, while it is well known that the solar cycle determines several properties of the heliosphere, the effects of the cycle on MC properties are not so well understood. In this work we review two major properties of MCs: (i) their expansion, and (ii) the magnetic flux and helicity that they transport through the interplanetary medium. We find that the amount of magnetic flux and helicity released via MCs during the last solar minimum (years 2007-2009) was significantly lower than in the previous one (years 1995-1997). Moreover, both MC size and mean velocity are in phase with the solar cycle while the expansion rate is weakly variable and has no relationship with the cycle. © 2012 International Astronomical Union.